Analyzing The Influence Of Corporate Financial Performance And Inflation On Stock Price Movements (An Empirical Study Of Mining Companies On The Indonesia Stock Exchange) - Aminul Amin (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the influence of internal financial variables—namely liquidity, solvency, and profitability—and external factors in the form of inflation on stock prices (Hrg_Shm) using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results of the path analysis indicate that the three internal variables have a positive influence on stock prices, but do not reach a statistically significant level (p-value > 0.05), indicating that a company's internal financial performance has a limited contribution in determining stock market valuations in the Indonesian economic context. Conversely, inflation is proven to have a positive and statistically significant impact (t-statistic > 1.96; p-value < 0.05), reflecting the role of moderate inflation as an indicator of economic growth expectations that drive stock price increases. The developed model has an R² value of 0.028, which indicates low explanatory capacity, underscoring the limitations of the variables used in explaining stock price fluctuations. The implication is that financial market practitioners are asked to consider macroeconomic factors—especially inflation stability—as a primary consideration in making investment decisions. As a direction for further research, it is recommended to use time-series data to strengthen the validity of the model and analyze the long-term dynamics of stock price movements in more depth.